Penerapan Program Crocodile Physics Sebagai Media Pembelajaran dalam Upaya Meningkatkan Pemahaman Konsep Fisika Siswa - Novianto, Abdi; Diana, Nirva (Indonesian Journal of Science and Mathematics Education, 2019)
Abstract:Research In this journal aims to find out the increasing students in understanding the conception of physics through the help of media Crocodile Physics programs. The form of research used in this study is Action Research. The population in this study amounted to 69 people consisting of 37 students in class VIII of SMP 1 Bandarlampung and 32 students in 32 students of class VIII A of SMP 25 Bandarlampung. To measure the students 'understanding of the concept, there were 3 cycles of tests with multiple choice questions 20 questions in each cycle. The results showed an increase in students' understanding of physics concepts seen from the percentage of learning outcomes completeness. Cycle I percentage of completeness in class VIII I is 40.54%, cycle II is 51.35 and in cycle III is 83.78%. Cycle I percentage of completeness in class VIII A is 18.75%, cycle II is 43.24% then in cycle III is 81.25%. Through the results of the analysis and discussion, it can be concluded that the use of the Crocodile Physics program is able to increase understanding of the concept of physics.Abstrak:Penelitian Pada jurnal ini memilikitujuan untuk mengetahui meningkatnya siswa dalam memahami konsepsi fisika melalui bantuan media programCrocodile Physics. Bentuk  penelitian yang digunakanpada penelitian ini adalah Action Research. Populasi dalam penelitian ini berjumlah 69 orang terdiri dari 37 peserta didik kelas VIII SMPN 1 Bandarlampung dan 32 peserta didik 32 peserta didik kelas VIII A SMPN 25 Bandarlampung. Untuk mengukur pemahaman konsep siswa dilakukan test sebanyak 3 siklus dengan soal pilihan ganda 20 soal dimasing-masing siklus.Hasil penelitian menunjukkan peningkatan pemahaman konsep fisika siswa di lihat dari presentase ketuntasan hasil belajar. Siklus I presentase ketuntasan dikelas VIII I sebesar 40,54 %, siklus II sebesar 51,35 dan pada siklus III sebesar 83,78 %. Siklus I presentase ketuntasan dikelas VIII A adalah 18,75 %, siklus II adalah 43,24 % kemudian pada siklus III adalah 81,25 %. Melalui  hasil analisis dan pembahasan dapat menyimpulkan untuk  penggunaan program Crocodile Physics mampu dalam meningkatnya pemahaman konsep fisika.